Saving and loan associations vs. commercial banks in Estonia: Responses to the financial crisis - Egle Tafenau (European Regional Science Association (ERSA), 2015)
The aim of the paper is to analyze the development of the Estonian credit and saving market, especially considering the sector of households and non-financial corporations, in order to reveal the potential of saving and loan association (SLA) to enhance the economic and social development outside of the main economic centers of Estonia. We show that the SLAs and commercial banks have developed differently during the latest years, with cut-backs in the amount of issued loans by the commercial banks, while the SLAs have increased their corresponding activity. The period of analysis is 2004-2014, as the data for the SLAs is only available since 2004. Moreover, the period covers the pre-crisis period of loan boom triggered by the commercial banks, as well as the crisis itself. We rely on the data of the Bank of Estonia. Unfortunately, only consolidated data is available, such that it is not possible to analyze the regional distribution of the issued loans. The developments in the loans issued by the financial institutions as well as deposits with them are discussed in the context of changed legal environment and general economic situation. Though the share of loans issued by the SLAs is still tiny in Estonia, it cannot be concluded that their total contribution to the economic development of rural areas is significant. However, in light of the recent fast growth in the deposits and loans by the SLAs, their relevance is expected to increase in the future. This is especially the case if they manage to take over the niche left by the commercial banks that have closed down their offices in small towns.
Keywords: G21; R10; 330; Saving and loan associations; transition economies; financial crisis